PARADIGMA KONSEP IMAM SHOLAT MASYARAKAT DESA KARANG ANYAR MENURUT PERSPEKTIF AL-QUR’AN DAN HADITS - Fadilatun Nisa Assayuti; Khoirunnisa Habib; Riski Suriani Lubis; Zainabila Zainabila (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
The word imam comes from the word al-qashdu which means goal or direction. In addition, Imam also means at-Taqaddum which means moving forward. According to the term, what is meant by imam in prayer is a person whose prayer is followed by other praying people with the conditions specified in the Sharia. In the Qur'an, the words imam (leader) and aimmah (leaders) are mentioned. This research uses descriptive qualitative research method. Qualitative research methods use the natural environment, where research is carried out in natural situations in a whole so that the data sources obtained directly are naturalistic. From the results of the research that has been carried out there are still many people who do not understand about prayer priests, especially the Hamlet VII-B area, KarangAnyar Village, Beringin District, Deli Serdang Regency. Therefore, this study focuses on discussing the concept of imam praying.